2021
DOI: 10.1002/psc.3388
|View full text |Cite
|
Sign up to set email alerts
|

Substrate plasticity of dehydratase SpaKC from the biosynthesis of thiosparsoamide

Abstract: Thioamitides are a group of ribosomally synthesized and post‐translationally modified peptides that possess diverse bioactivities and are usually featured by thioamide and 2‐aminovinyl‐cysteine (AviCys) motifs. In natural product thiosparsoamide, the AviCys motif is formed by an enzyme cascade formed by the flavin‐dependent decarboxylase SpaD and dehydratase SpaKC. SpaKC is a lanthipeptide synthetase homolog located outside the thiosparsoamide biosynthetic gene cluster. In this study, we show that SpaKC does n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Structural characterizations of the class V lanthipeptides lexapeptide, cacaoidin, and pristinin A3 demonstrated that each of these natural products contains a C-terminal AviCys, while the latter two also contain an N-terminal (Me)­Lan. ,, Several of the biosynthetically related thioamitides, such as thiosparsoamide, thioholgamide, thiostreptamide S4, and thioviridamide, also contain a C-terminal Avi­(Me)­Cys. While the corresponding biosynthetic clusters for each of these class V lanthipeptides encode LanK and LanY enzymes that catalyze dehydration of Ser/Thr, they all lack a lanthionine cyclase involved in the ring formation for compounds from classes I–IV.…”
Section: Introductionmentioning
confidence: 99%
“…Structural characterizations of the class V lanthipeptides lexapeptide, cacaoidin, and pristinin A3 demonstrated that each of these natural products contains a C-terminal AviCys, while the latter two also contain an N-terminal (Me)­Lan. ,, Several of the biosynthetically related thioamitides, such as thiosparsoamide, thioholgamide, thiostreptamide S4, and thioviridamide, also contain a C-terminal Avi­(Me)­Cys. While the corresponding biosynthetic clusters for each of these class V lanthipeptides encode LanK and LanY enzymes that catalyze dehydration of Ser/Thr, they all lack a lanthionine cyclase involved in the ring formation for compounds from classes I–IV.…”
Section: Introductionmentioning
confidence: 99%
“…The identification of this class of microbial specialized metabolite prompted biotechnological and pharmaceutical research to study different aspects of the thioamitides. Numerous works in recent years provided important information on the biosynthetic origin of these molecules, and on the enzymatic mechanisms underlying the extensive post-translational changes characterizing thioamitides [ [7] , [8] , [9] , [10] , [11] , [12] ]. Other studies have simultaneously investigated the biological potential of these peptides, highlighting the interesting cytotoxic activity that has grabbed the attention of cancer research [ [13] , [14] , [15] ].…”
Section: Introductionmentioning
confidence: 99%